Stunting on Children Aged 6 – 23 Months in East Nusa Tenggara Province - Wulandary, Weny; Sudiarti, Trini (Jurnal Kesehatan Masyarakat, 2024)
Stunting is the impaired growth and development that children experience from chronic malnutrition, repeated infection, poor maternal health, and inadequate psychosocial stimulation. The focus of this study is determinants of stunting of 6 – 23 months children in East Nusa Tenggara Province using data from the Study of Indonesian Nutritional Status in 2021. This research is a quantitative study that uses a cross-sectional design. The results showed that the proportion of stunting in 6-23 months in NTT province was 32.8%. The results of the bivariate analysis showed that variables significantly associated with stunting included child age (OR: 1.723 CI 95% 1.215-2.445), gender (OR: 1.777 CI 95% 1.305-2.419), LBW (OR: 2.106 CI 95% 1.206-3.423), SBL (OR: 1.768 CI 95% 1.133-2.759), history of infectious disease (OR: 1.548 CI 95% 1.141-2.099), maternal education (OR: 1.555 CI 95% 1.136-2.127), and toilet sanitation (OR: 1.881 CI 95% 1.384-2.555). The results of multivariate analysis showed that the most dominant factor of stunting was a history of infectious diseases (p-value 0.003; OR: 2.244). Children who have a history of infectious diseases are at risk of stunting by 2.2 times higher than children who do not have a history of infectious diseases after being controlled by child age, gender, LBW, SBL, and toilet sanitation.